The Effect of Acid Types in Cuka Pempek on The Surface Roughness of Acrylic Resin Denture Base - Khairina Labaika; Sri Wahyuningsih Rais; Febriani (Sriwijaya Journal of Dentistry, 2025)
Introduction: Cuka pempek is a typical Palembang food that contains acid as one of its ingredients. Continuous consumption of cuka pempek can affect the surface roughness of hot polymerized acrylic resin denture bases due to its ability to absorb liquids. Purpose: To determine the effect of acid types in cuka pempek on the surface roughness of hot polymerized acrylic resin denture bases. Methods: Thirty plates of hot polymerized acrylic resin measuring 65mm x 10mm x 2,5mm were divided into 3 groups. The initial surface roughness value (pretest) was calculated using a surface roughness tester. Soaking was carried out on group I (tamarind-based cuka pempek), group II (vinegar acid-based cuka pempek), and group III (control) with distilled water. Soaking was carried out for 30 hours in an incubator at 37°C. Measurement of the final surface roughness (post-test) was carried out. Results: The results of the normality test with the Shapiro-Wilk and the Levene test homogeneity test showed that the data were found to be normally distributed and homogenous. The paired t-test showed significant differences in all groups. The results of the one-way ANOVA test showed a significant difference. The results of the Bonferroni post hoc test showed a significant difference between tamarind-based and vinegar acid-based cuka pempek against distilled water, while there was no significant difference between tamarind-based and vinegar acid-based cuka pempek. Conclusion: There is an effect of the type of acid in cuka pempek on the surface roughness of the hot polymerized acrylic resin denture base.